Eat local, taste global : how ethnocultural food reaches our tables - Filson, Glen C., 1947-; Adekunle, Bamidele (Wilfrid Laurier University Press, 2017)
"Eat Local, Taste Global: How Ethnocultural Food Reaches Our Tables shows how the demand for ethnocultural vegetables on the part of Toronto's South Asian, Chinese, and Afro-Caribbean Canadians is at odds with the corporate food regime. How does that regime affect the local food movement and ethnic groups' access to their preferred foods? This book addresses that question and suggests that the protection of ethnic and national food security and sovereignty strengthens immigrant integration while producing healthy crossover effects for other Canadians."--